Книга перемен: [трилогия] / Дмитрий Вересов - Вересов Дмитрий (Семейный альбом, 2007)
Экземпляры: ф.23 (2008) / Инвентарный номер: 52515 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: В 31 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44